2023
DOI: 10.3390/cryst13040692
|View full text |Cite
|
Sign up to set email alerts
|

Intrafibrillar Growth of Hydroxyapatite Nanocrystals in Multiscale Collagen

Abstract: Collagen fibrils hierarchically assemble from microscale to macroscale, which endows the natural composite bone with good mechanical properties and remodeling functions. Revealing the intrafibrillar growth process of hydroxyapatite nanocrystals of collagen will guide the research of bone repair or collagen-based composites. Herein, we investigated the mineralization of multiscale collagen matrices and strongly proved the intrafibrillar hydroxyapatite nanocrystals in the collagen fibrils. The hydroxyapatite nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…SAED can be used to describe crystal orientation and composition, measure lattice constants, and determine any defects (Figure 4). Xue et al used both HRTEM and SAED for the characterization of intrafibrillar HA nanocrystals of MCFs in vitro [137]. The usefulness of XRD In the identification of HA crystals is undeniable.…”
Section: Characterizing Ha Crystalsmentioning
confidence: 99%
“…SAED can be used to describe crystal orientation and composition, measure lattice constants, and determine any defects (Figure 4). Xue et al used both HRTEM and SAED for the characterization of intrafibrillar HA nanocrystals of MCFs in vitro [137]. The usefulness of XRD In the identification of HA crystals is undeniable.…”
Section: Characterizing Ha Crystalsmentioning
confidence: 99%
“…The result indicated that the c-axis of the crystal was all parallel to the long axis of collagen fibers, which is similar to the collagen-mineral arrangement in nature. 5,24,57 In addition, the ultrathin section of PAA-COL + CPAM-SBF was prepared to expose its internal structure. The TEM image (Fig.…”
Section: àmentioning
confidence: 99%